2019
DOI: 10.4054/demres.2019.41.18
|View full text |Cite
|
Sign up to set email alerts
|

Migration influenced by environmental change in Africa: A systematic review of empirical evidence

Abstract: BACKGROUND Despite an increase in scholarly and policy interest regarding the impacts of environmental change on migration, empirical knowledge in the field remains varied, patchy, and limited. Generalised discourse on environmental migration frequently oversimplifies the complex channels through which environmental change influences the migration process. OBJECTIVE This paper aims to systematise the existing empirical evidence on migration influenced by environmental change with a focus on Africa, the contine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 104 publications
(176 reference statements)
2
92
0
1
Order By: Relevance
“…Yet, there is little consensus concerning the direction and the extent to which these factors influence migration. Environmental change has been found to contribute to increased human migration in some studies, whereas no effect or a decline in migration has been reported in others [9][10][11][12][13][14] . The empirical results differ depending on the environmental factors considered, the data and scale of the analysis, the methodology employed, and the geographical contexts covered.…”
mentioning
confidence: 90%
“…Yet, there is little consensus concerning the direction and the extent to which these factors influence migration. Environmental change has been found to contribute to increased human migration in some studies, whereas no effect or a decline in migration has been reported in others [9][10][11][12][13][14] . The empirical results differ depending on the environmental factors considered, the data and scale of the analysis, the methodology employed, and the geographical contexts covered.…”
mentioning
confidence: 90%
“…Together, these results suggest that to understand environmental migration in the northern highlands, we must account for household factors at the microlevel in combination with mesolevel factors such as agro-ecological characteristics. However, the available evidence in this regard is inconsitent, not least because mesolevel migration drivers are thus far underrepresented in the literature (Borderon et al, 2019). In addition, and similar to empirical studies in other regions of the world, the approaches either stick to qualitative migration narratives or do not have sufficient in-depth case-specific knowledge to explain how all the different influencing factors actually interact and how their interactions may enable or hamper migration.…”
Section: Environment-related Migration In the Northern Ethiopian Highmentioning
confidence: 99%
“…One main reason for the difficulty of grasping the complex interactions is the methods that are commonly utilized in empirical studies of environment-migration linkages: mostly, either quantitative large-N or qualitative small-N approaches are applied,. Qualitative research designs potentially allow for high explanatory power for factor interactions because they are based on sound knowledge of the local context and thus enable the analyses to tackle complex migration narratives (Borderon et al, 2019). However, they tend to be criticized for lacking replicability and generalizability (e.g., Bilsborrow and Henry, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As the current study suggests, environmental change cannot be viewed as the sole driver of migration. It is suggested that environmental impacts susceptible of triggering migration are mediated through factors on the macro, meso, and micro levels which include economic, social, and political drivers [61].…”
Section: Discussionmentioning
confidence: 99%